Systematic review and metaanalysis of lymph node metastases of resected pancreatic neuroendocrine tumors - Tanaka, Masayuki; Heckler, Max; Mihaljevic, André Leopold; Probst, Pascal; Klaiber, Ulla; Heger, Ulrike; Schimmack, Simon; Büchler, Markus W.; Hackert, Thilo (Annals of surgical oncology, 2021)
The optimal surgical strategy for pancreatic neuroendocrine tumors (PNETs) is unknown. However, current guidelines recommend a watch-and-wait strategy for small nonfunctional PNETs (NF-PNETs). The aim of this study is to investigate the risk stratification and prognostic significance of lymph node metastasis (LNM) of PNETs to guide decision-making for lymphadenectomy.